Differences between private intermediation in employment and providing information services about employment through telecommunications systems - Barański, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
Provisions of art. 18 (1) point 1 and art. 18c (2) point 4 of the Act on promotion of employment and labour market institutions of 20 April 2004, due to their far-reaching imprecision, raise the question what the mutual relationship between these provisions is, in particular, whether the services listed in Article 18c (2) point 4 of the mentioned Act fall within the conceptual scope of private intermediation in employment, or, on the contrary, they constitute services that cannot be classified as private intermediation in employment. The article analyzes in detail the regulations related to collecting (in the form of an electronic document) and providing information about employment through telecommunications systems. The difference between passive and active intermediation in employment has been shown, and an attempt has been made to indicate the legal regime of the contract for provision of services listed in art. 18c (2) point 4 of the mentioned Act.